Preparation and application of testosterone sensor using polyurethane membranes by square wave stripping voltammetry - Cemre Zeynep Harman; Öznur Güngör (Macedonian Journal of Chemistry and Chemical Engineering, 2022)
A novel electrochemical sensor for testosterone detection has been prepared by the chemical modification of a gold electrode (AuE). For the electrode modification, specific polyurethane (PU) films were synthesized from hexamethylene diisocyanate, olivetol, polyethylene glycol-100 (PEG100) and β-cyclodextrin. The synthesized PUs were investigated as selective films, and were used to coat a AuE surface at different concentrations and thicknesses. The testosterone responses of the modified electrodes were investigated by square-wave voltammetry (SWV). One separated cathodic SWV peak was obtained for testosterone at –0.390 V, with the prepared PU-modified AuE in 0.1 M phosphate buffer (PB) (pH 7.2). The linearity of testosterone responses of the prepared PU modified electrode was obtained over a concentration range of 0.1–1.0 µM (R2 = 0.995). It was observed that the response of the electrode increased regularly and sensitively with increasing testosterone amount. The detection limit, relative standard deviation and sensitivity of modified electrode were found to be approximately 5.69 nM, 1.669 % and 98.331 %, respectively. The PU-modified AuE exhibited good selectivity and a low response time for testosterone. Therefore, the prepared testosterone sensor offers a good alternative for fast and practical testosterone determination in clinical or biomedical studies.